The Spanish and Portuguese Systems: Two Examples Calling for a Further Reform – Uncovering the Architecture Underlying the New Consumer ADR/ODR European Framework - Esteban De La Rosa, Fernando (2022)
The article scrutinizes the European Framework for consumer ADR and ODR with the purpose of uncovering how Europe aims to develop ADR and ODR in EU MS in order to deliver justice and ensure a better enforcement of EU consumer protection rules and a better functioning of the markets. It deepens on the transformations in the ADR systems required to better fulfil the new functions assumed by the certified ADR entities and the role that the technology may play inside efficient certified consumer ADR entities. The domestic implementation of EU law in Spain and Portugal rather seems to perpetuate the pre-existing systems although wrapped up in European packaging with a ribbon on top. The exam reveals the existence of a further path for improvement and for obtaining additional advantages that could lead to a better functioning of the markets and a more suitable encompass with the philosophy that underlies the EU Regulatory Framework. The article explores different ways to move forward and achieve a higher degree of compliance with the ADR/ODR Regulatory Framework